Climate Change Activism Among Latino and White Americans - Ballew, Matthew T.; Goldberg, Matthew H.; Rosenthal, Seth A.; Cutler, Matthew J.; Leiserowitz, Anthony (Frontiers in Communication, 2019)
Research indicates that Latinos have particularly strong pro-environmental attitudes and support for policies to reduce climate change. This study explores differences in climate change activism (i.e., contacting government officials) between Latino and non-Latino White citizens in the United States, and the individual and social factors that predict engagement. Two parallel, nationally representative surveys find that Latinos (n = 1,433) are more likely than Whites (n = 861) to report having contacted a government official in the past and are more willing to contact officials in the future. Key predictors of Latinos’ significantly higher levels of political engagement include greater risk perceptions, egalitarian worldviews, pro-environment injunctive norms, collective political efficacy, and greater social network effects. Competitive mediation analyses find that stronger risk perceptions best predict differences in climate change activism between Latinos and Whites. Climate change communicators might particularly seek to amplify Latinos’ pro-climate tendencies (e.g., heightened risk perceptions) and social norms to encourage greater climate action by this vital and growing segment of the U.S. population.